Influences of ultrasonic treatment on structure and functional properties of salt‐soluble protein from Moringa oleifera seeds. (19th July 2021) - Du, Qiu‐Han; Wu, Yan‐Hui; Tang, Shi‐Qi; Ren, Min‐Hong; Fu, Zhen
Summary: Influences of ultrasonic treatment on structure and functional properties of salt‐soluble protein from Moringa oleifera seeds (MOSSP) were explored. The results indicated that the ultrasonic treatment destroyed spherical structure of MOSSP and transformed the spherical structure into irregular fragments. The content of β‐turn, α‐helix and random coils in MOSSP significantly increased, but with extending the ultrasound time, the content of β‐turn, α‐helix and random coils had no significant change. SDS‐PAGE results showed that sonication could stabilise the primary structure of MOSSP. The surface hydrophobicity and emulsification were significantly reduced, but sonication could improve the solubility and foaming properties of MOSSP within a certain range. Abstract : The spherical structure of salt‐soluble protein from Moringa oleifera seeds (MOSSP) was destroyed by ultrasonic treatment and transformed into irregular fragments. Sonication stabilised the primary structure of MOSSP, changed the secondary structure and tertiary structure and significantly weakened the H0 of MOSSP. Due to the changes in structure, the emulsification and solubility were improved. The results could provide a certain practical significance for potential utilisation of MOSSP.